Peningkatan Kesiapan Siswa Menghadapi SNBT melalui Program Sosialisasi dan Pendampingan Strategis - Arianto, Halil; Syamsinar, Syamsinar; Sa’diyyah, Fadhilah Nur; Ismiyati, Nur; Asfyra, Intan Buhati (Program Studi Manajemen FEB UNM, 2026)
Students’ readiness in facing the Seleksi Nasional Berdasarkan Tes (SNBT) is a crucial factor in determining their success in entering higher education. However, many students still lack optimal readiness, both in cognitive and non-cognitive aspects. This community service activity aims to improve students’ readiness through a program of socialization and strategic mentoring. The method used consists of preparation, implementation, and evaluation stages. The implementation includes SNBT socialization, strategic mentoring through guided practice and problem discussion, test simulation (try out), and motivation and mental strengthening sessions. Evaluation was conducted using questionnaires and observations to measure changes in students’ readiness levels. The results indicate a significant improvement in students’ understanding of the SNBT system, problem-solving skills, time management, self-confidence, and mental readiness. This program proves to be effective in enhancing students’ readiness comprehensively. Therefore, structured and continuous mentoring programs are recommended as a strategic effort to prepare students for higher education entrance examinations. Keywords: Student Readiness, SNBT, Socialization, Strategic Mentoring, Community Service